(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
This article discusses the history of the origin of Rishton pottery, the composition of the product, the patterns used, the stages of preparation, and the activities of well-known master potters. In general, he emphasizes the importance of Rishton pottery as a permanent cultural artifact that has stimulated the development of tourism in Central Asia, and it should be preserved and promoted in order to sustainably develop tourism.